2005
DOI: 10.1086/432002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapeutic Immunization on HIV‐1 Viremia after Discontinuation of Antiretroviral Therapy Initiated during Acute Infection

Abstract: Treatment strategies that would induce durable virological control of human immunodeficiency virus (HIV)-1 in the absence of continued antiretroviral therapy (ART) are highly desirable.METHODS. We assessed, in a randomized, double-blind, placebo-controlled trial, whether the addition of therapeutic vaccines (ALVAC-HIV [vCP1452] or ALVAC-HIV and Remune) to ART initiated during acute infection could increase the probability of having a plasma viral load Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 30 publications
1
80
0
Order By: Relevance
“…Early therapy was hypothesized to work by limiting the damage to the immune system. Despite evidence of immunogenicity of therapeutic vaccination, some studies did not show substantial virologic benefit (10,18). Therapeutic vaccination of persons treated with ART early after infection showed evidence of an induction of immune responses, but the magnitude and dynamics of virus rebound after therapy discontinuation was similar in both vaccinated and unvaccinated subjects (18).…”
Section: Rhesus Macaques Chronically Infected With Highly Pathogenic mentioning
confidence: 99%
“…Early therapy was hypothesized to work by limiting the damage to the immune system. Despite evidence of immunogenicity of therapeutic vaccination, some studies did not show substantial virologic benefit (10,18). Therapeutic vaccination of persons treated with ART early after infection showed evidence of an induction of immune responses, but the magnitude and dynamics of virus rebound after therapy discontinuation was similar in both vaccinated and unvaccinated subjects (18).…”
Section: Rhesus Macaques Chronically Infected With Highly Pathogenic mentioning
confidence: 99%
“…Along the same line, various vaccine strategies have been proposed to help restimulate HIV-specific immunity allowing HIV-infected patients to reduce time on antiretroviral therapy (ART) [7,8]. Various therapeutic vaccine candidates including peptide-, protein-, and viral vector-based vaccines have shown modest efficacy in experimental animal models [9,10] and patients [11][12][13][14][15][16][17][18]. Some candidate vaccines, such as ALVAC or Ad5, have induced potent increase in HIV-specific immune responses [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…25 Despite measurable immune responses being induced in both trials upon vaccination there was no correlation between immunogenicity and viral control during ATI. 11,25 Contrary to these results upon vaccination of chronically HIV-infected patients with the canarypox vector vCP1433 and the lipopeptides HIV-LIPO-6T followed by three cycles of IL-2 enhanced viral control of the vaccinated group was observed that correlated with the measured immune response. 26 In summary the FC was demonstrated to be safe and well tolerated in patients with HIV-1 infection.…”
Section: Discussionmentioning
confidence: 59%
“…There was no significant difference between placebo and active groups in their ability to control HIV viral replication in the ATI. 11 Comparable results were observed upon vaccination of a similar patient group with vCP1452 + gp160. 25 Despite measurable immune responses being induced in both trials upon vaccination there was no correlation between immunogenicity and viral control during ATI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation